Ефективність бізнес-планування інвестиційних проектів в сучасних умовах розвитку України - Сиром'ятникова, Оксана Валеріївна (НТУ "ХПІ", 2017)
Ефективна діяльність суб’єктів господарювання в довгостроковій і середньостроковій перспективі визначається рівнем їх інвестиційної активності. Інвестиції стають підґрунтям для прискорення науково-технічного прогресу, здійснення політики розширеного відтворення, стимулювання розвитку галузей національної економіки, вирішення соціальних і екологічних проблем та ін. Визначено, що одним з найбільш ефективних інструментів управління інвестиційною діяльністю є бізнес-планування, яке потребує комплексного підходу до оцінки його ефективності.

The effective activity of business entities in the long-term and medium-term perspective is determined by the level of their investment activity. Investments become the basis for accelerating scientific and technical progress, implementing the policy of expanded reproduction, stimulating the development of national economic sectors, solving social and environmental problems, etc. Business planning of an investment project is necessary for successful investment attraction and is one of the most effective instruments for managing investment activity. When drawing up a business plan for economic entities of each specific industry, it is necessary to approach individually. This will determine the formulation of the purpose of developing a business plan, the characteristics of its structure, the composition, number and content of sections. Only simultaneous use of static, dynamic and alternative methods for evaluating the effectiveness of investment projects will allow to obtain a reliable estimate of investment business planning and to fully assess the factors influencing the investment project and the effect of its implementation. The shortcomings of the existing methods indicate the need for their adaptation to the conditions of economic management of the national economy.
Efficiency business planning of investment projects in modern terms of development of Ukraine
Keywords: інвестиційний проект; бізнес-план; діяльність підприємства; бізнес-середовище; економічна ефективність